2020
DOI: 10.1007/s00063-020-00712-0
|View full text |Cite
|
Sign up to set email alerts
|

Zusammenarbeit von Intensivmedizin und Palliativmedizin

Abstract: Zusammenarbeit von Intensivmedizin und Palliativmedizin Eine Bestandsaufnahme an den deutschen onkologischen Spitzenzentren Die patientenorientierte Behandlung von Intensivpatienten hat weit mehr zum Ziel als die reine Lebenszeitmaximierung. Für die bestmögliche Versorgungsqualität und Lebensqualität können die Patienten von einer engen Zusammenarbeit zwischen der Intensivstation und der Palliativmedizin profitieren [18-20]. Doch wie gestaltet sich bislang der Brückenschlag zwischen der Intensivmedizin und Pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Such underlying diseases may facilitate the involvement of sPC. Here the tasks of palliative care lie in recovery and maintenance of quality of life [ 5 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such underlying diseases may facilitate the involvement of sPC. Here the tasks of palliative care lie in recovery and maintenance of quality of life [ 5 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This makes it clear that interdisciplinary collaboration between intensive medicine and palliative medicine needed to be improved in the study center. A descriptive study from Germany conducted at 16 Comprehensive Cancer Centres (CCC) showed that cooperation between intensive care and palliative care is not only a local but also an overarching problem (49). In 2016, the median of intensive care patients with palliative care consultations was 33 (minimum 0, maximum 100), only nine patients (median) were transferred from an intensive care unit to a palliative care unit (minimum 1, maximum 30).…”
Section: Discussionmentioning
confidence: 99%
“…In den letzten Jahren widmeten sich einige Publikationen der Überversorgung und Therapiebegrenzung in der Intensivmedizin [ 18 , 22 ] und erhöhten hier womöglich das Bewusstsein für die Sinnhaftigkeit der Integration palliativmedizinischer Aspekte in die Intensivmedizin [ 3 , 5 , 8 , 18 , 19 , 21 – 23 ]. Der Wechsel von einem kurativen zu einem palliativen Konzept bzw.…”
Section: Hinführung Zum Themaunclassified